POLA KOMUNIKASI ANTARA PEMBINA ASRAMA PUTRI DAN SANTRI DI UNIT PEMBINAAN SANTRI (UPS) PONDOK PESANTREN MODERN AL-JUNAIDIYAH BIRU BONE - A. Fajar Awaluddin (Al-Din: Jurnal Dakwah dan Sosial Keagamaan, 2018)
Communication is central to everything that activities performed daily to the public, ranging from office, education, relationships, sales and others. Many problems-problems concerning the group will be able to be traced, in the event that there is poor communication due to congestion and communication barriers, or because there is no communication at all. In writing this essay will discuss the problem of how communication patterns of teachers and pupils in schools. The focus in this study is the pattern of communication between teacher and student in the classroom at the Extraordinary Elementary School. This study uses descriptive qualitative analysis obtained from interviews, observation, and documentation. Communication patterns of teachers and pupils in UPS Al-Junaidiyah Biru at Bone Meulaboh is the teacher-student, student-teacher and student-student. This is because the number of students that a little, then take the initiative to collect student teacher in the classroom so that the teacher could total in giving attention to students when teaching and learning process. The pupils so feel free to ask or materials that are less obvious yet well understood and can be used to place teachers outpouring students.Keywordscommunication patterns; Teachers; Students; Pesantren Modern; Al-Junaidiyah Biru; Bone